2004
DOI: 10.1179/016164104225014058
|View full text |Cite
|
Sign up to set email alerts
|

Extension of ischemic therapeutic time window by a free radical scavenger, Edaravone, reperfused with tPA in rat brain

Abstract: 3-methyl-1-phenyl-2-pyrazolin-5-one (Edaravone) is a free radical scavenger. We tested the hypothesis that combination treatment of Edaravone and recombinant tissue plasminogen activator (tPA) extends the therapeutic time window. Male Wistar rats were subjected to 1.5-, 3.0- or 4.5-hour middle cerebral artery (MCA) occlusion (MCAO) by a nylon thread. Animals were randomly divided into four groups. The Sham group rats were operated without MCAO and drug injection. In the Vehicle-treated group the same volume of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 26 publications
1
47
2
Order By: Relevance
“…On the other hand, experimental ischemia-reperfusion induced by temporary middle cerebral artery occlusion resulted in the production of the highly neurotoxic 4-HNE, thereby contributing to apoptosis, suggesting that, after severe ischemia-reperfusion, the effects of free radicals on the brain are marked. 20) Based on this report and another that the degree of brain damage by free radicals is determined by the amount of free radical production exceeding the existing antioxidant activity in vivo, 10) we speculate that the production of free radicals was very low in the present vibration experiment, as described above, and they caused minimal tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, experimental ischemia-reperfusion induced by temporary middle cerebral artery occlusion resulted in the production of the highly neurotoxic 4-HNE, thereby contributing to apoptosis, suggesting that, after severe ischemia-reperfusion, the effects of free radicals on the brain are marked. 20) Based on this report and another that the degree of brain damage by free radicals is determined by the amount of free radical production exceeding the existing antioxidant activity in vivo, 10) we speculate that the production of free radicals was very low in the present vibration experiment, as described above, and they caused minimal tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Certain research groups have reported that the administration of edaravone increased the survival rate, and inhibited alteplase-induced hemorrhagic transformation, blood-brain barrier damage and oxidative stress in the ischemic brains of rats, and hypothesized that edaravone may reduce the activity of matrix metalloproteinase-9 (MMP-9) (43)(44)(45)(46). In their study, Kano et al (47) reported that edaravone attenuated the extravasation of alteplase through the cerebral vessels in a rat model of AIS.…”
Section: Combination Therapy Using Alteplase and Edaravonementioning
confidence: 99%
“…In their study, Kano et al (47) reported that edaravone attenuated the extravasation of alteplase through the cerebral vessels in a rat model of AIS. Combination treatment with edaravone is therefore expected to extend the TTW for the use of alteplase (46). Furthermore, Isahaya et al (48) reported that edaravone treatment was associated with lower MMP-9 serum levels in patients with AIS.…”
Section: Combination Therapy Using Alteplase and Edaravonementioning
confidence: 99%
“…Only tPA is approved by the US Food and Drug Administration (FDA) for intravenous delivery within 3 h of symptom onset in treating ischemic stroke (6). However, only a small portion of ischemic stroke patients receive effective thrombolytic therapy due to the narrow therapeutic time window and the threat of hemorrhage (7). The earlier the intervention involvement, the more benefit the patient receives.…”
Section: Introductionmentioning
confidence: 99%